Démons et déments. Quand Détective enquête sur la folie - Marc Renneville (Criminocorpus)
This article aims to identify the place of the theme of madness in Detective news magazine. The period of publication of the magazine (1928-1940) by a subsidiary of the publisher Gallimard corresponds to a time when the assistance to the insane is the subject of a debate that exceeds the professional circle of psychiatrists. Arbitrary confinement, escape or exit of dangerous patient, new therapies and prevention of madness are all questions relayed by the national press. What about Detective? How did this news magazine treat madness? The first part of this article tries to account for the processes of representation of madness in the pages of Detective. The second focuses on the analysis of the only report published on this theme, signed by Louis Roubaud and published on 12 issues from November 1932 to 1933.